2001
DOI: 10.1104/pp.126.4.1438
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Is Involved in Abscisic Acid-Induced Stomatal Closure in Vicia faba  

Abstract: One of the most important functions of the plant hormone abscisic acid (ABA) is to induce stomatal closure by reducing the turgor of guard cells under water deficit. Under environmental stresses, hydrogen peroxide (H 2 O 2 ), an active oxygen species, is widely generated in many biological systems. Here, using an epidermal strip bioassay and laser-scanning confocal microscopy, we provide evidence that H 2 O 2 may function as an intermediate in ABA signaling in Vicia faba guard cells. H 2 O 2 inhibited induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
463
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 595 publications
(491 citation statements)
references
References 53 publications
22
463
1
5
Order By: Relevance
“…The ability of guard cells to generate H 2 O 2 has been demonstrated in Nicotiana tabacum, L. esculentum, and C. communis [38,39]. The finding that ABA promotes H 2 O 2 synthesis in A. thaliana and V. faba guard cells was a significant advance, which further highlighted the fact that endogenous H 2 O 2 acts as an intermediate signal in ABA signaling in guard cells [40,41]. In addition, H 2 O 2 has also been shown to mediate MJ-, salicylic acid (SA)-, cytokinin-, auxin-, ethylene-, elicitor-, high CO 2 concentrations-, CO-, and UV-B-regulated stomatal movement [27,38,39,4247].…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…The ability of guard cells to generate H 2 O 2 has been demonstrated in Nicotiana tabacum, L. esculentum, and C. communis [38,39]. The finding that ABA promotes H 2 O 2 synthesis in A. thaliana and V. faba guard cells was a significant advance, which further highlighted the fact that endogenous H 2 O 2 acts as an intermediate signal in ABA signaling in guard cells [40,41]. In addition, H 2 O 2 has also been shown to mediate MJ-, salicylic acid (SA)-, cytokinin-, auxin-, ethylene-, elicitor-, high CO 2 concentrations-, CO-, and UV-B-regulated stomatal movement [27,38,39,4247].…”
mentioning
confidence: 58%
“…Nevertheless, whether H 2 O 2 participates in S1P-induced stomatal closure is still unknown. The results that S1P and H 2 O 2 mediate ABA-induced stomatal closure [5,14,40,41,58] and S1P also reduces stomatal aperture [5,14], this study promoted us to investigate the effect of S1P on H 2 O 2 production in guard cells during darkness-induced stomatal closure. Our results indicated that exogenous S1P induced H 2 O 2 production, and that darkness caused S1P synthesis and H 2 O 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the parameters of chlorophyll fluorescence and photosynthetic activity, observed 7 days after finishing the drought period during R1 rehydration, were probably due to damage to the photosynthetic apparatus caused by ROS, including hydrogen peroxide (Miller et al 2010). Moreover, hydrogen peroxide is involved in abscisic acid-induced stomatal closure (Zhang et al 2001;Bright et al 2006;Miao et al 2006), which may be another reason for reduced photosynthetic activity after 7 days of R1 or R3 treatment.…”
Section: (D)mentioning
confidence: 99%
“…Therefore, it can be inferred that diuron had negative effects on net photosynthesis, probably as a result of damage to the leaf tissue after the production of peroxides in the inhibition of electron flow in OS II, which consequently induced the production of abscisic acid (ABA) and stomatal closure, because these effects reduce stomatal conductance and CO 2 in the inner space of the leaf (Zhang et al 2001;Tironi et al 2010). The reduction in leaf transpiration can also be a result of oxidative stress induced by the action of diuron.…”
Section: Resultsmentioning
confidence: 99%